The association between admission glucose levels and outcomes in adults admitted to a tertiary care hospital - Patrick Mcgrade; Shengping Yang; Kenneth Nugent (Greater Baltimore Medical Center, 2019)
Background: Hyperglycemia at the time of hospital admission has been associated with poor outcomes in several patient groups, but there is little information about this association in hospitalized patients with diverse diagnoses. Methods: We identified all adult patients admitted between 10/1/2015 and 9/30/2016 who had glucose levels measured during the first 24 h after admission to the hospital. Clinical information included age, gender, glucose levels, diagnoses based on ICD 10 discharge coding, length of stay (LOS), and mortality. Patients were classified into quartiles based on glucose levels and into clinically relevant glucose categories. Results: This study included 18,478 adult patients admitted to a tertiary care hospital. The median age was 53 years, the median LOS was 4 days, and the overall in-hospital mortality was 3.8%. The median admission glucose level was 117 mg/dL. Mortality increased in each glucose quartile; it was also highest in patients admitted with a glucose <55 mg/dL or with a glucose >200 mg/dL. The LOS was significantly shorter in patients in glucose quartiles 1 and 2. Conclusions: Admission glucose levels were associated with in-hospital mortality and LOS in this cohort of hospitalized patients. Attention to glucose levels can help identify patients at risk for poor outcomes.